2009
DOI: 10.1074/jbc.m805301200
|View full text |Cite
|
Sign up to set email alerts
|

Caloric Restriction Stimulates Revascularization in Response to Ischemia via Adiponectin-mediated Activation of Endothelial Nitric-oxide Synthase

Abstract: Caloric restriction (CR) can extend longevity and modulate the features of obesity-related metabolic and vascular diseases. However, the functional roles of CR in regulation of revascularization in response to ischemia have not been examined. Here we investigated whether CR modulates vascular response by employing a murine hindlimb ischemia model. Wild-type (WT) mice were randomly divided into two groups that were fed either ad libitum (AL) or CR (65% of the diet consumption of AL). Four weeks later, mice were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
111
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 41 publications
3
111
1
Order By: Relevance
“…95 CR also enhances recovery of blood flow in response to limb ischemia in WT mice, accompanied by increased levels of eNOS phosphorylation and plasma adiponectin. 96 The stimulatory actions of CR on revascularization and eNOS phosphorylation of ischemic limbs are abolished in APN-KO mice, and, furthermore, CR does not improve blood flow recovery in the ischemic limbs of eNOS-KO mice. 96 Thus, CR promotes revascularization in response to tissue ischemia via an AMPK-eNOS-dependent mechanism that is mediated by adiponectin.…”
Section: Therapeutic Approaches To Increasing Adiponectin Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…95 CR also enhances recovery of blood flow in response to limb ischemia in WT mice, accompanied by increased levels of eNOS phosphorylation and plasma adiponectin. 96 The stimulatory actions of CR on revascularization and eNOS phosphorylation of ischemic limbs are abolished in APN-KO mice, and, furthermore, CR does not improve blood flow recovery in the ischemic limbs of eNOS-KO mice. 96 Thus, CR promotes revascularization in response to tissue ischemia via an AMPK-eNOS-dependent mechanism that is mediated by adiponectin.…”
Section: Therapeutic Approaches To Increasing Adiponectin Productionmentioning
confidence: 99%
“…96 The stimulatory actions of CR on revascularization and eNOS phosphorylation of ischemic limbs are abolished in APN-KO mice, and, furthermore, CR does not improve blood flow recovery in the ischemic limbs of eNOS-KO mice. 96 Thus, CR promotes revascularization in response to tissue ischemia via an AMPK-eNOS-dependent mechanism that is mediated by adiponectin. Collectively, nutritional approaches aimed at increasing adiponectin production could be useful in the treatment of cardiovascular diseases.…”
Section: Therapeutic Approaches To Increasing Adiponectin Productionmentioning
confidence: 99%
“…Lithium-treated mice lost 10%-15% of their body weight over the 8-week treatment described above. To control for lithium-induced decreases in body weight, a weight-matched group was maintained by means of caloric restriction similar to that described previously (77,78). Briefly, we first measured the daily amount of chow taken by an equivalent group of untreated mice for 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…Rats subjected to chronic intermittent fasting after myocardial ischemia induction were more likely to survive, showed reductions in infarct size, and had increased expression of antiapoptotic proteins (Katare et al, 2009). Furthermore, CR upregulated angiogenic factors and increased capillary density after myocardial ischemia (Katare et al, 2009) and was also shown to accelerate revascularization in mice after hindlimb ischemia (Kondo et al, 2009). Some evidence suggests SIRT1 may have an important role in the ability of CR to provide protection against ischemia.…”
Section: Caloric Restriction Activates Sirtuins and Mediates Lifespanmentioning
confidence: 99%